Thoracolumbar myelopathies in pug dogs. (6th February 2023) - Wachowiak, Ian J.; Patterson, Jon S.; Winger, Kathryn M.; Smiler, Kathleen L.; Cole, Robert; Moon, Rachel; Kluz, Michael; Bartner, Lisa R.
Abstract: Background: Constrictive myelopathy (CM) involving a fibrous band around the spinal cord is a newly recognized disease in pug dogs. Objectives: To identify the frequency of CM based on diagnostic imaging supplemented with necropsy; to determine whether a relationship exists between the sites of CM and other described T3‐L3 myelopathies; and to determine the frequency of caudal articular process dysplasia (CAPD). Animals: Thirty‐two client‐owned pug dogs diagnosed with a chronic, progressive T3‐L3 myelopathy based on neurological examination performed by a board‐certified neurologist. Methods: This is a prospective study. All dogs underwent computed tomography (CT) and magnetic resonance imaging (MRI) reviewed by a board‐certified radiologist. Magnetic resonance imaging abnormalities were categorized into diseases; CM only, CM plus other non‐CM condition(s), or non‐CM condition. Sites of CAPD were reported on CT. Nineteen dogs underwent necropsy. Results: Magnetic resonance imaging revealed 3 dogs with CM only, 17 with CM plus at least 1 other myelopathy, 11 dogs with non‐CM myelopathies only, and 1 with no MRI abnormalities. Nineteen of 32 dogs had >1 myelopathy diagnosis on MRI whereas 15/32 had >1 site of spinal cord compression. All dogs had CAPD at >1 site in the T3‐L3 vertebral column on CT. Conclusions and Clinical Importance: Constrictive myelopathy affected more than half of pug dogs presenting with chronic thoracolumbar myelopathies. Most had multilevel disease, concurrent myelopathies, or both. There was no apparent relationship between anatomic locations of CAPD and most severe myelopathy or myelopathy type.